Will Australians pay for health care advice from a community pharmacist? A video vignette study - Sriram, Deepa; McManus, Alexandra; Emmerton, Lynne; Jiwa, Moyez (Elsevier, 2015)
Background: Large proportion of Australians have access to pharmacists' health advice at no cost. The impact of a proposed co-payment levy for general practitioner (GP) consultation by Australian government is unclear. This raises an interesting question about consumers' perceived value of health-related consultations. Objective: This survey of representative sample of Western Australians explores the hypothesis that Australians are willing to pay for advanced model of pharmacy consultation. Methods: Two videos illustrating current-services and quality-enhanced-service (QES) incorporating systematic assessment of symptoms and referral to GP if necessary, were used. Participants viewed videos online and completed a willingness-to-pay (WTP) questionnaire about their perception and WTP for each service. Logistic regression and McNemar tests were used to identify WTP groups. Results: Of the 175 respondents, one in nine (19/175, 11%) were willing to pay and (35/175) 20% might consider paying for advice at pharmacies as per current-practice. Almost one in four (49/175, 28%) were willing to pay and (47/175) 27% would consider paying for QES (McNemar Test P < 0.001). Conclusions: The majority of West Australians may be willing to pay for consultation at pharmacies that offers more private, time-intensive experience with documented GP referral where required. Further research is warranted to test WTP with actual customers to confirm these results.